Knowledge, attitudes, and practices of Saudi physicians regarding cervical cancer and the human papilloma virus vaccine - Sarah Almazrou; Basema Saddik; Hoda Jradi (Elsevier, 2020)
Background: Cervical cancer is considered the second most common type of cancer in women worldwide, with a reported 570,000 incident cases documented each year. Infection with certain types of the Human Papillomavirus (HPV) has been found to be associated with more than 99% of cervical cancers. The HPV vaccine can prevent HPV infection and most cases of cervical cancers; however the uptake of this vaccine remains low in Saudi Arabia. Physicians can play a vital role in providing their patients with objective information regarding the HPV vaccine, yet little is known about their knowledge, attitudes, and practices in this area. Materials and methods: We conducted a cross-sectional study in King Abdul-Aziz Medical City (KAMC), Central Region, Saudi Arabia where data were collected through an online questionnaire to assess the knowledge, attitudes, and practices of physicians. Results: Most physicians (61%) displayed a good level of knowledge about cervical cancer; 94% were knowledgeable of the causative link between (HPV) infection and cervical cancer. Family medicine physicians had better knowledge regarding cervical cancer, HPV, and HPV vaccination than pediatricians (p = 0.023). Physicians with >10 years of practice had better knowledge of cervical cancer than other respondents (p = 0.041). 80% of the sample thought it was important for women to receive the HPV vaccine and 82% stated they would allow their daughters to be given the HPV vaccine. Lack of parental knowledge of the vaccine was significantly (p = 0.034) associated with a lack of knowledge about HPV, and this was one of the most common barriers preventing recommendation of the HPV vaccine. Conclusion: With the increasing prevalence of HPV infections, better knowledge of HPV infection, HPV-related diseases, and the availability of HPV vaccinations from health professionals will assist with the implementation of effective prevention and treatment programmes. Keywords: Knowledge about cervical cancer, Knowledge about HPV, Physicians, Cervical cancer, HPV vaccine, Kingdom of Saudi Arabia